Henry Care, Roger L'Estrange and the Contested Memory of Erasmus and the Reformation in Restoration England: 2018 Roland Bainton Lecture - Dodds, Gregory D. (Erasmus studies, 2020)
Henry Care and Roger L'Estrange fought a bitter battle in the public press in Restoration England. Exploring the ways in which each employed the writings and reputation of Desiderius Erasmus provides insight into the deep fault lines dividing English society in the decade from 1678 to 1688. Their divergent uses of Erasmus demonstrate how late-seventeenth-century interpretations of the early sixteenth-century Reformation became critical points of conflict in the most significant political and religious debates of the period. Paying attention to the reception of Erasmus also helps explain how these two bitter enemies eventually joined William Penn in supporting James II's Indulgence for Liberty of Conscience.